The role of statins in dementia or Alzheimer’s disease incidence: a systematic review and meta-analysis of cohort studies - Du, Ye; Yu, Zhangjie; Li, Chengyi; Zhang, Yanxing; Xu, Buyun (Frontiers in Pharmacology, 2025)
BackgroundThe effect of statins on the risk of dementia and Alzheimer’s disease (AD) is unclear.MethodsWe systematically searched EMBASE, Web of Science, PubMed, CENTRAL and ClinicalTrail.gov for cohort studies comparing incidence of new-onset dementia and AD between statin users and non-users. We applied the DerSimonian–Laird random effects method to pool hazard ratio (HR) with 95% confidence intervals (CI).ResultsWe included forty-two studies comprising 6,325,740 patients. Thirty-five cohort studies involving 6,306,043 participants were pooled and indicated that statin use was associated with a reduced risk of dementia (HR: 0.79, 95% CI: 0.71–0.88). Similarly, an analysis of 19 studies comprising 1,237,341 participants demonstrated a 29% decrease in the risk of AD among statin users (HR: 0.71, 95% CI: 0.60–0.85). In sensitivity analyses, diagnostic criteria for dementia/AD significantly affected the combined risk estimates. In subgroup analyses, compared to studies enrolling participants with a mean/median age over 70 years, those younger than 70 years exhibited greater efficacy of statins in preventing dementia (HR: 0.67, 95% CI: 0.56–0.81 vs HR: 0.86, 95% CI: 0.78–0.95; P = 0.02) and AD (HR: 0.47, 95% CI: 0.44–0.50 vs. HR: 0.81, 95% CI: 0.71–0.92; P < 0.01). Due to significant heterogeneity in the definitions of statin dosage and exposure duration, pooling the results was abandoned and most studies suggested that higher dosages and longer exposure duration of statins further reduce the risk of dementia and AD.ConclusionStatin use is associated with a reduced incidence of dementia and AD, which might be modified by ages.